Promoting effective enforcement of the prohibition against corporal punishment in South African schools - Faranaaz Veriava (Pretoria University Law Press (PULP), 2014)
About the publication The prohibition against corporal punishment is an integral part of the broader transformation of South African education. The prohibition seeks to replace South Africa's violent and authoritarian past with an ethos respectful of human dignity and bodily integrity. About the editors: Faranaaz Veriava has a BA LLB from the University of the Witwatersrand and a LLM in human rights and constitutional practice from the Centre for Human Rights at the University of Pretoria. Table of Contents PREFACE ACKNOWLEDGMENTS EXECUTIVE SUMMARY ABBREVIATIONS AND ACRONYMS Introduction 1.1 The purpose of the report 1.2 Methodology 1.3 The structure of the report Corporal punishment in context 2.1 A historical overview of corporal punishment in South Africa 2.2 Debates on corporal punishment 2.3 An 'official ambivalence' to the prohibition The incidence of corporal punishment 3.1 An overview of statistical data 3.2 A sample study of corporal punishment complaints 3.3 Observations from the corporal punishment cases The legal and policy framework governing the prohibition against corporal punishment in South Africa 4.1 The protection of learners from corporal punishment 4.2 The sanction of educators administering corporal punishment 4.3 Best practice case studies: Western Cape and Gauteng Corporal punishment at independent schools 5.1 An overview of independent schools in South Africa 5.2 The legal framework governing independent schools 5.3 Improving mechanisms of enforcement at independent schools Developing effective 'legal and educational' programmes in enforcing the ban against corporal punishment 6.1 Shifting attitudes and implementing alternatives to corporal punishment 6.2 Improved mechanisms for the enforcement of the corporal punishment ban 6.3 Proposed interventions Conclusion LIST OF REFERENCES